Synthesis, structure and in vitro antiproliferative effects of alkyne-linked 1, 2, 4-thiadiazole hybrids including erlotinib- and ferrocene-containing derivatives. Issue 46 (25th August 2021) - Boulhaoua, Mohammed; Pasinszki, Tibor; Torvisco, Ana; Oláh-Szabó, Rita; Bősze, Szilvia; Csámpai, Antal
Abstract : Fourteen 1, 2, 4-thiadiazole derivatives were synthesized and structurally characterized; their in vitro antiproliferative activities were evaluated on four tumorous cell lines (U87, A2058, A431, and HepG2). Abstract : Chemotherapy is an indispensable tool to treat cancer, therefore, the development of new drugs that can treat cancer with minimal side effects and lead to more favorable prognoses is of crucial importance. A series of eleven novel 1, 2, 4-thiadiazoles bearing erlotinib (a known anticancer agent), phenylethynyl, ferrocenyl, and/or ferrocenethynyl moieties were synthesized in this work and characterized by NMR, IR and mass spectroscopies. The solid-phase structures were determined by single-crystal X-ray diffraction. Partial isomerisation of bis(erlotinib)-1, 2, 4-thiadiazole into its 1, 3, 4-thiadiazole isomer, leading to the isolation of a 3 : 2 isomer mixture, was observed and a plausible mechanism for isomerisation is suggested. The in vitro cytostatic effect and the long-term cytotoxicity of these thiadiazole-hybrids, as well as that of erlotinib, 3, 5-dichloro-1, 2, 4-thiadiazole and 3, 5-diiodo-1, 2, 4-thiadiazole were investigated against A2058 human melanoma, HepG2 human hepatocellular carcinoma, U87 human glioma, A431 human epidermoid carcinoma, and PC-3 human prostatic adenocarcinoma cell lines. Interestingly, erlotinib did not exhibit a significant cytostatic effect against these cancer cell lines. 1, 2, 4-Thiadiazole hybrids bearing one erlotinib moiety or both an iodine and a ferrocenethynyl group, as well as 3, 5-diiodo-1, 2, 4-thiadiazole demonstrated good to moderate cytostatic effects. Among the synthesized 1, 2, 4-thiadiazole hybrids, the isomer mixture of bis-erlotinib substituted 1, 2, 4- and 1, 3, 4-thiadiazoles showed the most potent activity. This isomer mixture was proven to be the most effective in long-term cytotoxicity, too. 3, 5-Diiodo-1, 2, 4-thiadiazole and its hybrid with one erlotinib fragment were also highly active against A431 and PC-3 proliferation. These novel compounds may serve as new leads for further study of their antiproliferative properties.